2006
DOI: 10.1007/s00264-006-0097-8
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of successful use of the Pavlik harness in infants with developmental dysplasia of the hip

Abstract: This study examined the outcomes of ultra-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
111
7
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(133 citation statements)
references
References 25 publications
10
111
7
5
Order By: Relevance
“…The reported success rate of Pavlik harness treatment in Graf Type III and IV hips is not as high as the other Graf hip types [3,16,21,22,25,31]. The results of the present study revealed that both a lower initial a angle and a worse Graf hip type decrease the Pavlik harness treatment success rate.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…The reported success rate of Pavlik harness treatment in Graf Type III and IV hips is not as high as the other Graf hip types [3,16,21,22,25,31]. The results of the present study revealed that both a lower initial a angle and a worse Graf hip type decrease the Pavlik harness treatment success rate.…”
Section: Discussioncontrasting
confidence: 59%
“…There are few data on the success rate of Pavlik harness treatment in ultrasonographic hip types other than Graf Type III and IV hips. The reported treatment success rate with the Pavlik harness is higher in such hips [3,9,31]. The success rate of Pavlik harness treatment was more than 90% in Graf Type IIa-hips, approximately three-fourths in Type IIb hips, and approximately two-thirds in Types IIc and D hips in the present study.…”
Section: Discussionsupporting
confidence: 40%
See 1 more Smart Citation
“…Greater than 90% success may be expected in hips that are stable on examination but dysplastic on ultrasound images [8] and for those dislocatable with the Barlow [3] maneuver [6,12,14,25]. However, treatment failures of 30% to 60% have been reported in dislocated reducible Ortolani-positive hips [2,14,16,19,20,24,[30][31][32]. Failure of the Pavlik harness method has been associated with an increased risk of osteonecrosis of the femoral head [29].…”
Section: Introductionmentioning
confidence: 99%
“…(2) What are the factors predictive of failure of Pavlik harness treatment for Ortolani-positive hips?…”
Section: Introductionmentioning
confidence: 99%